KOMPETENSI PEMASAR, KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP PEMBELIAN ULANG DENGAN MODERASI KEPUASAN KONSUMEN (Studi Kasus XSAVAY Advertising Solo) - Iphut Suparni; Supawi Pawenang; Istiatin Istiatin (JURNAL MANAJEMEN, 2019)
This research was conducted with the aim of (1) testing and analyzing the effect of simultaneous marketer competence, product quality, service quality, and customer satisfaction on the decision to repurchase XSAVAY Advertising Solo products, (2) testing and analyzing the influence of marketer competence, product quality, service quality, and customer satisfaction with the decision to repurchase XSAVAY Advertising Solo products and (3) testing and analyzing the effect of partial marketer competence, product quality, and service quality on the decision to repurchase XSAVAY Advertising Solo products with moderation of customer satisfaction. This research is a quantitative descriptive study, taking a population of 120 people, namely the number of consumers who purchase merchandise at XSAVAY Advertising from January 2018 until December 2018, and the number of samples is 92 respondents. The data collection method in this study used a questionnaire as a tool to obtain data regarding purchasing decisions. The results showed (1) there was a simultaneous effect of marketer competence, product quality, service quality, and customer satisfaction on the decision to repurchase XSAVAY Advertising Solo products, (2) there was a partial influence of marketer competence, product quality, service quality, and customer satisfaction towards the decision to repurchase XSAVAY Advertising Solo products and (3) there is a partial effect on marketer competence, product quality, and service quality, on the decision to repurchase XSAVAY Advertising Solo products with moderation in customer satisfaction.